Japanese working class lives : an ethnographic study of factory workers - Roberson, James E., 1955- (Routledge, 1998)
This ethnographic study examines the lives of Japanese workers in small firms and analysis their experiences of working life, leisure and education. This unique case study of the Shintani Metals Company illustrates the ways in which employees lives extend beyond their work. Japanese Working Class Lives provides a valuable alternative view of working life outside the large corporations. Roberson demonstrates that the Japanese working class is more diverse than Western stereotypes of be-suited salary-men would suggest.